MENINGKATKAN HASIL BELAJAR SISWA DENGAN METODE PROBLEM BASED LEARNING MATA PELAJARAN IPS KELAS VII-4 SMP NEGERI 8 TEBING TINGGI - Bernat Lubis (Universitas Negeri Medan, 2019)
The purpose of this study is to improve student learning outcomes in social studies subjects through the problem based learning method. This classroom action research was conducted in 2 cycles with four stages, namely: planning, implementation, observation, reflection. The subject of this study were students of class VII-4 of SMP Negeri 8 Tebing Tinggi as many as 36 students. This study used qualitative descriptive analysis techniques. Based on the data obtained from measurements in the form of learning completeness in the first cycle of 72.22% and the second cycle of 86.11% it was found that there was an increase in student learning outcomes. This means that social studies learning using the method of problem based learning can improve the learning outcomes of class VII-4 students at SMP Negeri 8 Tebing Tinggi. Key word : Problem based learning, social science, learning outcomes